How Significant Arabic Brand Name, Halal Logo and Manufacturer Country of Origin Image Trigger Consumer Purchase Decision on Halal Cosmetic - Utami Putri, Telisiah; ., . (International Journal of Engineering and Technology, 2018)
Halal cosmetic is becoming a trend, not only directly targeted to muslim women as main consumer but non-muslim women also set as a target. Halal cosmetic is not only perceived as a product that meets islamic laws and proper to be used by muslim woman but more than that, it is perceived as a product that provides good quality assurance, does not contain with harmful substances, safe and ethical products.Some aspects from manufacturer side thought to have significant role as a trigger in purchase decision towards halal cosmetic. This study explores the variabels of Arabic brand name, halal logo and manufacturer country of origin image to be addressed deepen to check how those variabels influence consumer positive perception that lead to purchase decision on halal cosmetic.This study is conducted via on-line survey by using WhatsApp mobile application in Surabaya. Respondents are women 20 â€“ 50 years old, muslim and non-muslim, users of mass-market cosmetic brand in IndonesiaCollected answers from 76 respondents within one week field project. The result of this study is expected to be a preliminary study used by cosmetic manufacturer as a reference to set up the most suitable product strategy to be competitive in halal cosmetic market.Â Â